Abu Ubaid's Contribution to the History of Islamic Economic Thought: A Conceptual Analysis of Al-Amwal and Its Relevance to Modern Economics - Ismail; Nurhudawi; Arifa Pratami (Penerbit Merdeka Kreasi, 2025)
This study discusses the Islamic economic thought of Abu Ubaid al-Qasim ibn Sallam (d. 224 AH/838 AD), one of the important figures in the classical Islamic intellectual tradition who made a major contribution to the formation of the concept of public finance and the distribution of wealth in Islam. The background of this research departs from the need to re-examine classical Islamic economic ideas that are relevant to contemporary economic issues, such as social inequality, distribution justice, and sharia-based fiscal policies. The purpose of this research is to examine in depth Abu Ubaid's thought as contained in his monumental work, Kitab al-Amwal, and to analyze its relevance to modern economic challenges. The method used in this study is a qualitative approach with the type of figure study, through a search of scientific literature obtained from Google Scholar and other credible academic sources. The data was analyzed using content analysis techniques, by examining the main themes in Abu Ubaid's work, such as zakat, kharaj, jizyah, baitul mal, and the principle of wealth distribution. The results of the study show that Abu Ubaid emphasizes the importance of social justice, economic equity, and the active role of the state in ensuring the welfare of the people through a fair public asset management system. His thinking is based on Islamic moral values which place wealth as a trust for the common good. In conclusion, Abu Ubaid's thoughts remain relevant in answering contemporary economic challenges, especially in building an Islamic economic system that is just, sustainable, and in favor of the welfare of the people.